Longitudinal analysis of cigar use patterns among US youth and adults, 2013-2019 - Jessica King Jensen; Gregory J. Stoddard; Cristine D. Delnevo; Julie W. Merten; Sunday Azagba (BMC, 2023)
Abstract Background Cigars are available in a range of pack quantities, which contrasts regulations requiring cigarettes to be sold in packs of 20 or greater. Smaller packages may be associated with increases in initiation while larger packs may lead consumers to smoke more. The purpose of this study was to inform pack quantity regulations by examining whether usual cigar pack quantity purchased was associated with use, initiation, and discontinuation among youth and adults for four cigar types: premium cigars, large cigars, cigarillos, and filtered cigars. Methods We analyzed waves 1-5 (2013-2019) of the adult and waves 2-5 (2014-2019) of the youth Population Assessment of Tobacco and Health (PATH) Study. Samples included those responding to the item on pack quantity and providing data at all waves (adults: premium cigars [N = 536], large cigars [N = 1,272], cigarillos [N = 3,504], filtered cigars [N = 1,281]; youth: premium cigars [N = 55], large cigars [N = 217], cigarillos [N = 1514], filtered cigars [N = 266]). Generalized estimating equation models examined the population-averaged effects of pack quantity on cigar use, initiation, and discontinuation. Results Adult pack quantity was positively associated with the days used per month for premium cigars (b: 0.23, 95% CI: 0.11, 0.34), large cigars (b: 0.17, 95% CI: 0.08, 0.25), cigarillos (b: 0.12, 95% CI: 0.003, 0.24), and filtered cigars (b: 0.07, 95% CI: 0.04, 0.10), and positively associated with amount smoked per day for all cigar types. Youth pack quantity was positively associated with days used per month for premium cigars (b: 0.88, 95% CI: 0.33, 1.43), large cigars (b: 0.79, 95% CI: 0.43, 1.15), and cigarillos (b: 0.17, 95% CI: 0.01, 0.34). Adult initiation was associated with pack quantity for filtered cigars (b: -2.22, 95% CI: -4.29, -0.13), as those who initiated purchased smaller pack quantities compared to those who did not initiate that wave. Pack quantity was not associated with discontinuation for adults or youth. Conclusions Cigar use increased as usual pack quantity purchased increased across cigar types for youth and adults. Small increases in pack quantity (e.g., one additional cigar) are likely to result in consuming less than one additional day per month, though larger increases (e.g., 10 additional cigars per pack) may result in greater use.